Overview Management Implementation Commitment and Occupational Health (OHS) at the Regional General Hospital Labuang Baji Makassar Year 2022 - Ricky Perdana P; Bulandari (Formosa Journal of Science and Technology, 2023)
Occupational accidents can occur in hospitals due to not optimal K3 management in hospitals. This study aims to find out how the Commitment to Implement Occupational Safety and Health (K3) Management in Hospitals is described. The research design used a descriptive qualitative method. The results of this study indicate that the commitment to implementing K3 management at Laburan Baji General Hospital Makassar has not been effective and has not been maximized. From the aspect of OHS Policy, the hospital is making an OHS policy, the hospital's OHS regulations and procedures are being improved, the hospital's OHS culture is not yet effective, the workforce's knowledge of hospital OHS is not maximized, and the hospital's OHS infrastructure is incomplete.